The Influence of Image Media on The Ability to Write Fairy Tales - Anggraeni, Sri Wulan; Alpian, Yayan; Prihadani, Depi; Nawawi, Heri (International Conference on Elementary Education, 2020)
The purpose of this study was to determine the effect of picture media on the ability to write fairy tales fourth-grade elementary school students. This research method is a quantitative method of experimentation with the Nonequivalent Control Group design. The sample of this study was 40 students. Data collection techniques through the ability to write fairy tale writing skills and data analysis techniques used descriptive statistics to measure the mean value consisting of the mean (mean), median and mode. Inferential Statistics consists of tests of normality, homogeneity, and T-test. The results showed that there was an influence of image media on the ability to write a fairy tale, it was seen that the significance value (sig.2-tailed) with t-test was a data analysis technique to test hypotheses carried out with calculations statistical t-test Paired Samples Test. The results of the research were obtained from the t-test calculation of Sig. (2-tailed) is 0,000 less than 0.05, so Hâ‚€ is rejected, meaning that there is an influence of the image media on the ability to write fairy tales